Ecological aspects of potential arbovirus vectors (Diptera: Culicidae) in an urban landscape of Southern Amazon, Brazil - Silva Pessoa Vieira, Carla Julia; Thies, Sirlei Franck; Ferreira Silva, David Jose; Kubiszeski, Janaina Rigotti; Barreto, Eriana Serpa; Oliveira Monteiro, Hamilton Antonio de; Mondini, Adriano [UNESP]; Steiner Sao Bernardo, Christine; Morais Bronzoni, Roberta Vieira de (Elsevier B.V., 2020)
Amazon has been under intense human pressure, especially in the so-called Arc of Deforestation in the Eastern and Southern regions. Changes in biodiversity due to landscape disturbance in municipalities at the Arc of Deforestation are likely to impact mosquito species leading to the potential for emergence of arboviruses. Our aim was to describe the composition and structure of culicids in Sinop, a municipality located in the Southern Amazon at the State of Mato Grosso, as well as their presence in urban habitats, analyzing climate variables and potential risk of arbovirus transmission. Mosquitoes were collected in four habitats located in urban environments for 12 months. We recovered 5,210 adult mosquitoes from mosquito traps. Among the 33 species identified, 19 are associated with arbovirus transmission. Higher abundance, richness, diversity, and equitability of mosquito species were observed in urban forest parks and in new neighborhoods located in the outskirts of the city, nearby forest fragments and agricultural areas. As the environment consolidates as urban, both abundance and richness decrease. Highly urbanized neighborhoods had higher dominance of Culex quinquefasciatus, a mosquito associated with different arboviruses, including West Nile and Saint Louis encephalitis virus. The medically important species Cx. declarator, Cx. (Melanoconion) ssp., Aedeomyia squamipennis and Aedes scapularis were found in the four habitats. It is possible that these mosquitoes are adapting to different habitats and as a consequence, they are reaching urbanized areas. Mosquito abundance was higher in the days of high temperature and low precipitation in urban forest parks and in highly urbanized neighborhoods. These results suggest that Sinop region is a key area for surveillance of arbovirus vectors.
Keywords: Entomological surveillance; Vector ecology; Arboviruses emergence